2022
DOI: 10.1007/s41133-022-00057-7
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Augmented Reality for Increasing the Awareness of Food Waste Amongst Dutch Consumers

Abstract: Food waste is a significant challenge, and our societal behaviours play a role in the amount of food items discarded. Thus, an effective method to inform consumers about high wastage patterns may help reduce the amount thrown away. This research investigates how Augmented Reality can be harnessed to enlighten consumers and work towards addressing high food waste patterns. Yet research on this topic is still very much in its infancy. To pursue this solution, food behaviour data are employed to provide an insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It was found that food waste generated from the retail distribution accounts for 7% (>7% for bread and oil, 5%–7% for fruits and vegetables, 1%–3% for frozen foods and sauces) of the total waste (Mena et al., 2011; Rodrigues et al., 2021). Immersive technologies like AR provide a visual aid in understanding the volume of waste generated (Honee et al., 2022). So, the foremost use of immersive technologies in the above‐mentioned areas is mainly involved in creating awareness and educating people.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that food waste generated from the retail distribution accounts for 7% (>7% for bread and oil, 5%–7% for fruits and vegetables, 1%–3% for frozen foods and sauces) of the total waste (Mena et al., 2011; Rodrigues et al., 2021). Immersive technologies like AR provide a visual aid in understanding the volume of waste generated (Honee et al., 2022). So, the foremost use of immersive technologies in the above‐mentioned areas is mainly involved in creating awareness and educating people.…”
Section: Introductionmentioning
confidence: 99%